2006
DOI: 10.1159/000095005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Serum GH Cut-Off Values for Pharmacological Tests of GH Secretion Depend on the Serum GH Method

Abstract: Background: The serum GH cut-off value for pharmacological tests of GH secretion (PhT GH) depends on the type of test and also on the method used for determining serum GH. Cut-off serum GH values as different as 5–10 ng/ml, have been reported, and have been validated biochemically. We have used the growth velocity (GV)-standard deviation score (SDS) during the first year of treatment with rhGH to validate these cut-offs on a biological basis. Methods: Fifty pre-pubertal patients with short stature (height ≤–2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…It must be considered in the analysis that, when Kowarski described the syndrome of bioinactive GH, serum GH levels were measured by radioimmunoassay using polyclonal antibodies that recognized all forms of serum GH; later on, monoclonal antibodies which measure the 22 Kd form were used. Moreover, the advent of methodologies based on the interaction with the GH receptor binding sites 13,14 reduced the chances of discrepancy between immunoreactivity and bioactivity. However, the finding of discrepancies between immuno-and bio-assays of serum GH still suggests the presence of mutations in the GH-1 gene that cause the production of GH oligomers with low biological activity 15 or abnormal post-translational processing of GH 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…It must be considered in the analysis that, when Kowarski described the syndrome of bioinactive GH, serum GH levels were measured by radioimmunoassay using polyclonal antibodies that recognized all forms of serum GH; later on, monoclonal antibodies which measure the 22 Kd form were used. Moreover, the advent of methodologies based on the interaction with the GH receptor binding sites 13,14 reduced the chances of discrepancy between immunoreactivity and bioactivity. However, the finding of discrepancies between immuno-and bio-assays of serum GH still suggests the presence of mutations in the GH-1 gene that cause the production of GH oligomers with low biological activity 15 or abnormal post-translational processing of GH 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…One interesting study showed that the cut-off value is based on the serum GH method. They concluded that a value of 10.8 ng/ml is the cut-off for a GH deficit diagnosis if the GH test is done by immunofluorometric assay [22]. We suggest caution with the interpretation of the GH test results and using them in association with the IGF-1 and IGFBP3 serum levels (using SDS corrected for age, sex and BMI).…”
Section: Discussionmentioning
confidence: 99%
“…GHD was defined as follows: maximum serum GH response less than 6.1 ng/mL (IRP IS80/505) or 4.7 ng/ml (IRP IS 98/5742) to 2 pharmacological tests [19,20] .…”
Section: Methodsmentioning
confidence: 99%